ДЕЦЕНТРАЛІЗАЦІЯ ГУМАНІТАРНОЇ ПОЛІТИКИ В УКРАЇНІ: ШЛЯХИ УДОСКОНАЛЕННЯ - Gradivskyi, Victor (Zhytomyr Ivan Franko State University, 2023)
The article states that among the main problems of the humanitarian sphere’s development at the regional level are the shortcomings of public administration’s the existing system, its centralized burden, inherited from the time of the command-administrative system. Several directions for improving humanitarian policy at the regional level have been identified: the first is decentralization of power (bringing management closer to its consumers, facilitating access to participation in making and monitoring the implementation of management decisions, simplifying public control over state expenditures and their results); the second - modernization of public management of the humanitarian sphere at the regional level (identification of fundamental spiritual values, achievement of understanding on the most acute problems of Ukraine's historical past, as historical experience and historical memory of all regions and all generations of Ukrainians); the third is humanitarian development and social equalization of regions (development of human potential: education, children's rights, health, culture, employment and social cohesion, gender equality), etc. It has been proven that modern humanitarian policy, like politics in other spheres of social life, is implemented today in the conditions of transformation of central authorities and decentralization of management. The main problems of the development of the humanitarian sphere at the regional level, according to the author, are the defects of the existing system of public administration, its centralized burden, inherited from the time of the command-administrative system. It was concluded that granting the maximum autonomy of the powers of local authorities to solve the problems of humanitarian development at their level is not only a reduction of the often unjustified influence of the center on the daily activities of local authorities, but also a strengthening of the initiatives of the latter, their activity and cooperation with by various subjects of humanitarian activity, which contributes to the democratization of the entire management system in the humanitarian sphere.